FLOWERING INITIATION IN ONION BULB CROP AS INFLUENCED BY TRANSPLANTING DATES AND NITROGEN FERTILIZER - N. H. Khan; S. M. Khan; N. U. Khan; A. Khan; A. Farid; S. A. Khan; N. Ali; M. Saeed; I. Hussain; S. Ali (Journal of Animal and Plant Sciences, 2019)
Bolting (pre-mature flowering) produced before completion of normal life cycle which directly affects the bulb yield in onion. The experiments were conducted in two consecutive seasons during 2013-14 and 2014-15 in a randomized complete block design (RCBD) replicated three times at Agricultural Research Institute, Mingora Swat. Nursery of onion cultivar Swat-1 was raised and healthy seedlings were transplanted on five different dates (15th Nov, 1st Dec, 15th Dec, 1st Jan, 15th Jan). Four levels of nitrogen fertilizer (75, 100, 125, 150 kg ha-1) were applied with the objective to determine its influence on inflorescence development in onion bulb crop. Bolting percentage gradually decreased with increase in nitrogen fertilizer. Maximum bolting percentage was recorded in early transplanting and gradually declined with delay in transplanting. Bolting incidence did not occurred in very late transplanting (15th Jan) irrespective of the rate of nitrogen applied. Plant height, stem thickness, bulb diameter, bulb weight and total yield increased with increase in nitrogen fertilizer and conversely showed a downward trend with delay in transplanting. Nitrogen doses didn’t significantly influenced leaves per plant. Early transplanting took maximum days to maturity than late transplanting. Maturity was delayed with increase in nitrogen fertilizer. Percent cull decreased with increase in the rate of nitrogen fertilizer. Marketable yield was maximum at mid transplanting (15th Dec) with maximum dose of nitrogen fertilizer. It can be concluded that 150 kg N ha-1 should be applied and transplanting should be delayed up to December 15th to avoid bolting and have maximum marketable yield.
Keywords: Allium cepa L.; Bolting; Nitrogen fertilizer; Transplanting; Marketable yield